Boundaries and Horizons of Realism in the Contemporary Painting of St. Petersburg - Gracheva, Svetlana M. (Actual Problems of Theory and History of Art, 2020)
In recent times, there has been a lot of discussions in St. Petersburg’s artistic community about problems of modern realistic fine arts. Even more obvious is the confrontation between different trends of fine arts promoting themselves as “contemporaries”. The problem of modern realism does exist.This is a broad term which implies dozens of directions and methods in art and diversity of its interpretations. Along with traditions, there are novelties in modern realism that are linked to a wider range of achievements of national and world culture. These include the experience of the artistic avant-garde, modernism and postmodernism of the 20th century, the influence of contemporary art trends and even participation of artists-adherents of Academism in contemporary art events. In the contemporary artworld of St. Petersburg, there is a generation of artists who do not seek to break away from the academicschool, but they are keenly aware of the need to update their artistic language. They are not radical, and they do not deny the principles of imaging, figurativeness, and picturesqueness in realistic art works.They have reached a high level of craft, but they feel dissatisfaction from the art limited to formal experiments and distanced far from the reality. Looking at the works of these artists, a viewer involuntarily compares them with each other, trying to find their place in the modern art scene. Notably, the artists borrowed much from the academic school, having learned the lessons of their mentors — masters of St. Petersburg fine arts. However, this is a very special view of the world and art that transforms reality. Our modern postindustrial, post-informational, postmodern world has also formed a new vision of reality demonstrated by the artists of the 2010s.